In Vivo Study on the Role of Taraxacum Officinale in Modulating Paracetamol-Induced Hepatotoxicity - Obaid , Asmaa; Al-Jumaili , Farah T. O.; Makia , Raghda S. (American Journal of Biology and Natural Sciences, 2025)
Taraxacum officinale is widely used to address various illnesses. This study aimed to explore its key phytochemical components and evaluate the impacts of its methanolic extract on paracetamol-induced hepatotoxicity in mice, in addition to conducting histological analysis of liver tissue. Phytochemical screening revealed that the plant contains varying amounts of flavonoids, tannins, saponins, alkaloids, and polyphenols, relying on the solvent used, with the methanolic extract exhibiting the maximum concentration of total flavonoids (210.2 ± 25.7 mg/g). Biochemical analysis and histological examination of liver sections in the positive control group (mice given paracetamol) showed that paracetamol induces hepatotoxicity, as evidenced by increased blood levels of AST, ALT, ALP, and MDA and reduced catalase levels. Liver sections also revealed zonal acute cellular swelling of hepatocytes, perivascular infiltration of lymphocytes and macrophages, and necrotic hepatocytes. On the other hand, these markers were reduced in mice that dealt with the plant extract. Hence, it can be stated that Taraxacum officinale demonstrates hepatoprotective activity against paracetamol-induced hepatotoxicity and may be a promising therapeutic option for drug-induced liver damage.